(untitled) (Economic journal of Lesya Ukrainka Volyn National University, 2022)
Abstract. Intellectual property objects are the driving force in the development of science and technology. The problem of accounting of intellectual property objects in the context of attribution of authorship on someone else’s development and application of effective means of protection of innovation product in conditions of unfair competition is actualized. The main task of the enterprise innovation development is to form its accounting and analytical support, which should help to expand the possibilities of forming and using their innovative potential, that is why the work is urgent and timely. Systematized accounting accounts and typical holding, which can be used for purchase and sale of licenses. The analysis of introduced innovations and patents was carried out. The reasons of decrease of the number of registered objects of intellectual property were revealed. The focus is on know-how as an object of intangible assets and the main forms of documentary confirmation of the introduction and disposal OF the object ON are systematized. Methodological recommendations on patent registration have been developed.